Effect of organic management on the diversity and function of arthropods associated with cacao (Theobroma cacao L.) in Colombia - Dorado Suárez, Juan Camilo; Merle, Isabelle; Requier, Fabrice; Dupas, Stephane (Revista Colombiana de Entomología, 2025)
Cacao (Theobroma cacao L.) is a high-value commercial crop from which the popular chocolate is derived. Despite its importance, little is known about the associated arthropods and the factors affecting their diversity and functional dynamics. On the other hand, organic farming systems are considered a solution for biodiversity conservation. Consequently, this study aims to compare the abundance and diversity of arthropods, along with their functional roles, evaluating differences between conventional and organic systems. The study was conducted in Nilo, Cundinamarca, Colombia, comparing six conventional and organic cacao plots. Pitfall, interception, Malaise, and floral glue traps were used to recollect arthropods each day over three days in three sampling periods, each attempting to capture a phenological phase of cacao. A total of 273 arthropod families and 15,310 individuals were identified and categorized based on their ecological roles. The results indicate a significant increase in arthropod abundance in organic plots. Additionally, at the functional role level, an effect was found on the abundance of each plot. However, according to the inverse Simpson index, no differences in diversity were found between conventional and organic systems. A negative effect of temperature and precipitation on arthropod abundance was observed across several functional roles. These findings highlight the dynamics of the entomofauna in cacao and how organic management can benefit biodiversity. However, further research is needed to assess its impact on production and societal benefits.